Integrative multi-omics summary-based mendelian randomization identifies key oxidative stress-related genes as therapeutic targets for atrial fibrillation and flutter - Chen, Shijian; Sun, Junlong; Wen, Wen; Chen, Zhenfeng; Yu, Ziheng (Frontiers in Genetics, 2024)
Background Atrial fibrillation (AF) is a prevalent cardiac arrhythmia associated with substantial morbidity and mortality. Oxidative stress (OS) has been implicated in the pathogenesis of AF, suggesting that targeting OS-related genes could offer novel therapeutic opportunities. This study aimed to identify causal OS-related genes contributing to AF through a comprehensive multi-omics Summary-based Mendelian Randomization (SMR) approach. Methods This study integrated data from genome-wide association studies (GWAS) with methylation quantitative trait loci (mQTL), expression QTL (eQTL), and protein QTL (pQTL) to explore the relationships between oxidative stress-related (OS-related) genes and AF risk. Genes associated with oxidative stress and AF were obtained from the Nielsen et al. study (discovery) and the FinnGen study (replication). The SMR analysis and HEIDI test were utilized to assess causal associations, followed by Bayesian co-localization analysis (PPH4 > 0.5) to confirm shared causal variants. Multi-omics data were employed to analyze the associations within mQTL-eQTL pathways. A two-sample MR analysis was conducted for sensitivity verification. The significance of findings was determined using a false discovery rate (FDR) < 0.05 and p_HEIDI > 0.01. Results At the DNA methylation level, 19 CpG sites near 7 unique genes were found to have causal effects on AF and strong co-localization evidence support (PPH4 > 0.70). At the gene expression level, six oxidative stress-related genes from eQTLGen and three from GTEx (v8), including TNFSF10, CDKN1A, ALOX15, TTN, PTK2, ALB, KCNJ5, and CASQ2, were found to have causal effects on AF in the sensitivity and co-localization analyses (PPH4 > 0.50). At the circulating protein level, both ALAD (OR 0.898, 95% CI 0.845–0.954, PPH4 = 0.67) and APOH (OR 0.896, 95% CI 0.844–0.952, PPH4 = 0.93) were associated with a lower risk of AF, and APOH was validated in the replication group. After integrating the multi-omics data between mQTL and eQTL, we identified two oxidative stress-related genes, TTN and CASQ2. The methylation of cg09915519 and cg10087519 in TTN was associated with higher expression of TTN and a lower risk of AF, which aligns with the negative effect of TTN gene expression on AF risk. TTN may play a protective role in AF. Conclusion This study identified several OS-related genes, particularly TTN, as having causal roles in AF, which were verified across three-omics pathways. The findings underscore the importance of these genes in AF pathogenesis and highlight their potential as therapeutic targets. The integration of multi-omics data provides a comprehensive understanding of the molecular mechanisms underlying AF, paving the way for targeted therapeutic strategies.